Acute medicine : a practical guide management of medical emergencies - Sprigings, David; Chambers, John (John Boyd) (UK: Wiley Blaekwell, 2018)
"Acute Medicine offers an accessible and concise guide to the practical management of all acute medical problems likely to be encountered in the emergency department, ambulatory care centre, acute medical unit or on the wards. Reflecting the maturation of acute medicine as a separate specialty, the book is divided into common presentations, specific problems and procedures. New to the fifth edition is a chapter on bed-side ultrasonography; throughout, emphasis is placed on patient safety, and the use of flow diagrams, tables and figures ensures that key information is quickly accessible. Thoroughly revised by experts in the subject, and updated to reflect current approaches to diagnosis and management, Acute Medicine is an excellent companion for the trainee as well as an aide-mm̌oire for the more experienced physician"--Provided by publisher.
Machine generated contents note: Contributors Preface Evolution of Acute Medicine: the development of Ambulatory Emergency Care Section 1: PRESENTATIONS IN ACUTE MEDICINE General 1 The critically ill patient 2 Hypotension and shock 3 Reduced conscious level 4 Delirium 5 Falls in older people Cardiorespiratory 6 Cardiac arrest 7 Acute chest pain 8 Palpitations 9 Transient loss of consciousness 10 Acute breathlessness 11 Acute respiratory failure 12 Pleural effusion 13 Cough and haemoptysis Neurological 14 Neurological diagnosis in acute medicine 15 Acute headache 16 Seizures and epilepsy 17 Weakness and paralysis 18 Acute sensory symptoms 19 Loss of vision Abdominal 20 Acute vomiting 21 Acute abdominal pain 22 Acute diarrhoea 23 Acute jaundice 24 Ascites 25 Acute kidney injury Skin and Musculoskeletal 26 Acute rash 27 Urticaria and angioedema 28 Acute arthritis 29 Acute spinal pain 30 Acute limb pain Miscellaneous 31 Comprehensive geriatric assessment 32 Acute medical problems in pregnancy 33 Fever on return from abroad 34 Acute medical problems in the HIV-positive patient Section 2: SYNDROMES AND DISORDERS General 35 Sepsis 36 Poisoning 37 Acid-base disorders 38 Anaphylaxis Cardiovascular 39 Acute arrhythmias: general principles of management 40 Regular broad complex tachycardia 41 Irregular broad complex tachycardia 42 Narrow complex tachycardia 43 Atrial fibrillation and flutter 44 Bradycardia and atrioventricular block 45 Acute coronary syndromes 1: ST-segment elevation 46 Acute coronary syndromes 2: Non-ST-segment elevation 47 Acute pulmonary edema 48 Acute heart failure and decompensated chronic heart failure 49 Cardiogenic shock 50 Aortic dissection and other acute aortic syndromes 51 Heart valve disease and prosthetic heart valves 52 Infective endocarditis 53 Acute pericarditis 54 Cardiac tamponade 55 Severe hypertension 56 Deep vein thrombosis 57 Pulmonary embolism 58 Problems with pacemakers and other cardiac devices 59 Upper airway obstruction 60 Acute asthma 61 Exacerbation of chronic obstructive pulmonary disease (COPD) 62 Community-acquired pneumonia 63 Hospital-acquired pneumonia 64 Pneumothorax 65 Stroke 66 Transient ischaemic attack 67 Subarachnoid haemorrhage 68 Bacterial meningitis 69 Encephalitis 70 Spinal cord compression 71 Guillain-Barre syndrome 72 Raised intracranial pressure 73 Acute upper gastrointestinal bleeding 74 Acute lower gastrointestinal bleeding 75 Acute oesophageal disorders 76 Inflammatory bowel disease flare 77 Acute liver failure and decompensated chronic liver disease 78 Alcoholic hepatitis 79 Biliary tract disorders and acute pancreatitis 80 Urinary tract infection 81 Hypoglycaemia 82 Hyperglycaemic states 83 Diabetic ketoacidosis 84 Hyperosmolar hyperglycaemic state 85 Disorders of plasma sodium concentration 86 Disorders of plasma potassium concentration 87 Disorders of plasma calcium concentration 88 Disorders of plasma magnesium concentration 89 Disorders of plasma phosphate concentration 90 Acute adrenal insufficiency 91 Thyrotoxic storm 92 Myxedema coma 93 Pituitary apoplexy 94Paraganglioma (phaeochromocytoma) crisis 95 Cellulitis and necrotizing fasciitis 96 Erythroderma and toxic epidermal necrolysis 97 Acute gout and pseudogout 98 Septic arthritis 99 Acute vasculitis 100 Interpretation of full blood count and film 101 Pancytopenia and Febrile neutropenia 102 Bleeding disorders 103 Management of anticoagulation 104 Acute painful sickle cell crisis 105 Complications of cancer 106 Alcohol-related problems in acute medicine 107 Hypothermia 108 Drowning 109 Electrical injury 110 Palliative and end-of-life care 111 Medicolegal issues in Acute Medicine 112 Airway management 113 Non-invasive ventilation Section 3: TECHNIQUES AND PROCEDURES IN ACUTE MEDICINE 114 Ultrasonography in Acute Medicine 115 Reading a chest X-ray 116 Central vein cannulation 117 Arterial blood sampling and cannulation 118 Arterial blood gases, oxygen saturation and oxygen therapy 119 Temporary cardiac pacing 120 Pericardial aspiration (pericardiocentesis) 121 DC cardioversion 122 Insertion of an intercostal chest drain 123 Lumbar puncture 124 Aspiration of the knee joint 125 Insertion of a Sengstaken-Blakemore tube.
Preceded by Acute medicine / David Sprigings, John Chambers. 4th ed. 2008.
Includes bibliographical references and index.
Keywords: Emergencies; Emergency Treatment -- methods; Handbooks